PENGEMBANGAN PEMERTAHANAN BAHASA JAWA MELALUI BUDAYA LOKAL GUYUB TUTUR DALAM KAJIAN ANTROPOLINGUISTIK - Tabrani, Akhmad T; Prasetyoningssih, Luluk Sri A (LITERA, 2017)
Abstract This study aims to yield a product for the Javanese language maintenance through local culture in speech community in an anthropolinguistic study. This research and development study used the Recursive, Reflective, Design, and Development (R2D2) design. The development procedure consisted of four steps, i.e. designing a prototype, testing the prototype (through expert judgment and field testing), revising the prototype, and in a large scale producing a DVD of the Javanese language maintenance through local culture in speech community. The data were analyzed by means of expert judgment and field testing using the mean score analysis technique. The research and development product is a DVD of the Javanese language maintenance through local culture in speech communitysatisfying the acceptability requirement. The product becomes an official document for the local government and related parties as a reference for the Javanese language maintenance. The Java language as part of local culture is a cultural heritage that must be preserved. To preserve local culture, cultural maintenance against external influences is necessary by completely, authentically, and officially documenting it. Keywords: Javanese language maintenance, local culture, speech community, anthropolinguistics